PERAN PELATIHAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA DALAM MENINGKATKAN KUALITAS KERJA KARYAWAN TINJAUAN LITERATURE REVIEW - Alfi Magvery; Dian Nirmasari (Paser Institute Management and Busines, 2023)
This research was conducted to find out the role of training and human resource development in improving work quality. The research method used was a literature review, articles were collected by searching using Google Scholar. The criteria for articles used are those published in 2018-2023. Based on the articles collected, the results showed that human resources are a very important asset for a company in supporting the achievement of company goals, so it is a necessity and necessity for companies to improve employee abilities and competencies through training and development. Training is an effort to increase short-term capabilities, while human resource development is an effort to increase employee competency in the long term.